Corporate Social Responsibility Against NGO’s Advocacy: The Case of Wilmar International towards Greenpeace - Luthfiani, Novera; Hidayatullah, Nur Luthfi (Universitas Airlangga, 2025)
This study is conducted to fill the gap of the literature regarding how a Multinational Corporation’s (MNC) corporate social responsibility (CSR) strategy, in this case Wilmar International can be used to stop the pressure from Non-Governmental Organizations’ (NGOs) advocacy, such as Greenpeace. The use of CSR is generally done as a form of corporate compliance with the government and responsibility to the local society. The researchers argue that Wilmar International’s CSR could be used to stop pressure from Greenpeace, although not for a long time. In this study, the researchers used a descriptive qualitative method to explore this case, with literature studies from various journal articles, as well as data from documents in the form of reports from Wilmar International and Greenpeace. After conducting an in-depth analysis of Wilmar’s various responses to Greenpeace, it has been proven that Wilmar fulfills all aspects of CSR. On the economic and philanthropic aspects, it is still not enough to stop the pressure from Greenpeace. Nevertheless, the legal and ethical aspects of Wilmar International’s CSR has successfully stopped Greenpeace’s pressure. This study found that when MNCs have implemented CSR tangibly with transparency, it could be used to stop the pressure of NGOs’ advocacy. Keywords: Wilmar International; Greenpeace; Corporate Social Responsibility; Multinational Corporation; Non-Governmental Organization.